Postulowany model wspólnoty oraz dobra wspólnego w publikacjach katolickiego tygodnika społecznego „Ład” w latach 1981–1984 - Tasak, Agata (Polityka i Społeczeństwo, 2021)
The paper focuses on the analyses of the socio-political concepts presented in the Catholic social weekly Ład in the years 1981–1984. In the period under question, the periodical was a media platform which enabled the expression of views by lay Catholics who perceived opportunities for increasing their socio-political activity in the political reality of Poland at that time. The model of community proposed by them, as well as the way of defining the common good, were for the most part consistent with the concepts of the social teaching of the Catholic Church and conformed to the guidelines of the hierarchs of the Catholic Church in Poland – especially Primate Stefan Wyszyński. The calls to action for the common good were combined with the idea of reconciliation, dialogue, and cooperation. Accordingly, the national community was thus considered the most important community of all. It should be emphasized that these concepts were supposed to enhance the power and importance of this particualt community of Catholics in public life and to contribute to establishing their position as the most important representative of the Catholics on the political scene of the period.